EGFR fluorescence in situ hybridisation assay: guidelines for application to non-small-cell lung cancer. Issue 11 (27th October 2009) - Varella-Garcia, M; Diebold, J; Eberhard, D A; Geenen, K; Hirschmann, A; Kockx, M; Nagelmeier, I; Rüschoff, J; Schmitt, M; Arbogast, S; Cappuzzo, F
Abstract : There is a need for predictive biomarkers that identify non-small-cell lung cancer (NSCLC) patients most likely to respond to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) treatment. There are numerous potential candidates, although none has been proven in prospective clinical trials. The EGFR gene copy number evaluated by fluorescence in situ hybridisation (FISH) has been highlighted as one of the most effective markers for sensitivity to EGFR TKIs in large phase III, randomised placebo-controlled trials and has been used in clinical settings to assist physicians in defining the therapeutic regimen. The EGFR FISH assay has technical challenges and it is critical that detailed guidelines are provided to help clinical laboratories in performing and interpreting the test. Excellent assay reproducibility and portability rates among laboratories are crucial to guarantee that accurate clinical decisions can be made for patients with NSCLC. This article discusses the consensus outcomes of a global workshop convened to discuss key technical issues and standardise reading strategies for the EGFR FISH assay of NSCLC tumour tissue.